The Position of Australia in the Global LNG Market and its Prospects - Basiubina, Polina; Bolotov, Ilya; Zeynalov, Ayaz; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis explores the global LNG market with a particular focus on Australia’s LNG industry. It aims to identify the key trends in the global LNG market and the position that Australia occupies in this market. The thesis analyses factors behind the global LNG industry expansion, key market participants performing exports and imports of LNG, as well as actions that the LNG industry takes to keep up with the global decarbonization agenda. The thesis further dives into the examination of Australia’s LNG industry development by identifying important factors spurring its massive growth. It also provides an analysis of the current state of the industry in the country with an emphasis on major challenges faced by the industry elaborating on aspects such as regulatory environment and domestic gas market. Furthermore, the thesis examines Australia’s potential for green energy export alternatives in the context of global green energy transition. An analysis of the aforementioned aspects is conducted through the utilization of secondary data, and for the identification of Australia’s position in the global LNG market and its prospects, a SWOT analysis is applied.
Vedoucí práce: Ilya Bolotov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses